Predicting the macroseismic intensity from early radiated P wave energy for on‐site earthquake early warning in Italy. Issue 10 (30th October 2015) - Brondi, P.; Picozzi, M.; Emolo, A.; Zollo, A.; Mucciarelli, M.
Abstract: Earthquake Early Warning Systems (EEWS) are potentially effective tools for risk mitigation in active seismic regions. The present study explores the possibility of predicting the macroseismic intensity within EEW timeframes using the squared velocity integral (IV2) measured on the early P  wave signals, a proxy for the P wave radiated energy of earthquakes. This study shows that IV2 correlates better than the peak displacement measured on P waves with both the peak ground velocity and the Housner Intensity, with the latter being recognized by engineers as a reliable proxy for damage assessment. Therefore, using the strong motion recordings of the Italian Accelerometric Archive, a novel relationship between the parameter IV2 and the macroseismic intensity (IM) has been derived. The validity of this relationship has been assessed using the strong motion recordings of the Istituto Nazionale di Geofisica e Vulcanologia Strong Motion Data and Osservatorio Sismico delle Strutture databases, as well as, in the case of the MW 6, 29 May 2012 Emilia earthquake (Italy), comparing the predicted intensities with the ones observed after a macroseismic survey. Our results indicate that P wave IV2 can become a key parameter for the design of on‐site EEWS, capable of proving real‐time predictions of the IM at target sites. Key Points: Novel on‐site methodology for Italy using IV2 is derived IV2 can be used for real‐time predictions of macroseismic intensity EEW intensity maps derived by IV2 allow the mitigation of seismic risk